PENGARUH STRATEGI PENGELOLAAN MODAL USAHA DAN STRATEGI PEMASARAN PADA UMKM DALAM MENINGKATKAN PROFITABILITAS - Lifchatullaillah, Endang; Supeni, Nely; Legiyanti, Indra (BISMA: Jurnal Bisnis dan Manajemen, 2024)
One of the economic strengths in Indonesian economy is MSMEs or Micro, Small and Medium Enterprises which are growing and developing in society and resulting in significant growth after the Covid 19 Pandemic. This research aims to analyze the influence of business capital management and marketing strategies in increasing profitability of MSMEs. The population in this study were MSMEs in the Jember Lor area, Jember. Samples were drawn using cluster sampling techniques in accordance with specified criteria. The questionnaire for data collection consists of 8 (eight) question items which were measured using a Likert scale. The collected data was then analyzed using multiple linear regression. The results of the analysis show that there is an influence of business capital management strategies and marketing strategies in increasing profitability.